Sharp Efficiency for Vector Equilibrium Problems on Banach Spaces. (27th March 2013) - Li, Si-Huan; Wang, Qiang; Xu, Shu; Wang, Jun-Xiang
Abstract : The concept of sharp efficient solution for vector equilibrium problems on Banach spaces is proposed. Moreover, the Fermat rules for local efficient solutions of vector equilibrium problems are extended to the sharp efficient solutions by means of the Clarke generalized differentiation and the normal cone. As applications, some necessary optimality conditions and sufficient optimality conditions for local sharp efficient solutions of a vector optimization problem with an abstract constraint and a vector variational inequality are obtained, respectively.